Pengaruh Kualitas Genetik Sapi Lokal Terhadap Efisiensi Penggemukan Di Sumatera Utara - Ahmad Fauzan; Fachri Tarmizi; Bagus Arya Darma; Ali Putra Siregar; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study investigated the effect of genetic quality of local North Sumatra cattle on fattening efficiency. PCR and RFLP-based genetic analyses and fattening efficiency measurements through average daily growth (ADG) and feed conversion (FCR) were used. local cattle from Deli Serdang, Langkat, and Simalungun were used. The study showed that feed management involving the use of concentrate and high-quality forage can improve cattle fattening efficiency, and the IGF-1 gene plays a significant role in cattle growth. A strong correlation between fattening efficiency and genetic quality (r = 0.85) indicates the importance of genetic selection to improve productive local cattle. Based on these findings, it is recommended to implement molecular marker-based genetic selection programmes and improve feed management by diversifying local feed sources. In addition, it is necessary to improve farmer training on more efficient husbandry methods. This research provides policy suggestions that can be implemented to support the curiosity of the livestock industry in North Sumatra and improve the efficiency of local cattle production.